Bucovina as an Example of Central European Linguistic Contacts) - Artur Tworek (Linguistische Treffen in Wrocław, 2025)
The following review article discusses Helena Krasowska’s monograph “Polish Highlanders in Carpathian Bucovina: A Sociolinguistic and Lexical Study” from 2024, which draws on the Polish-language version published in 2006 but updates and expands upon it. The main idea of the publication is the analysis of language contact in a multiethnic and multilingual Central European region: Bukovina. Present-day Bukovina is divided into two states: the northern part of the region lies in Ukraine, and the southern part in Romania. In addition to Ukrainian and Romanian, German and Russian were also historically present there. To this day, Polish, as a minority language, remains an integral part of Bukovina’s linguistic landscape, both in Ukraine and Romania. In the first chapters, the author presents the history of the region and examines the migration processes that determine the current ethnic and linguistic landscape of the territory. The author examines the Polish dialects in six villages – three Ukrainian (Stara Huta, Terebleche, and Niyhni Petrivtsi) and three Romanian (Soloneţu Nou, Pleşa, and Poiana Micului). The analyses are conducted from a sociolinguistic perspective, observing the functional uses of Polish in those villages. A separate chapter thoroughly examines and presents the lexical dialect material (including phonetic and morphological annotations). A typology of linguistic contacts between Polish and other languages in Bukovina is also proposed.